2020
DOI: 10.1002/ejic.201900956
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Extraction of Trivalent f‐Cations Using Several N‐Pivot Tripodal Diglycolamide Ligands in an Ionic Liquid: The Role of Ligand Structure on Metal Ion Complexation

Abstract: Complexation of trivalent lanthanides and actinides was studied in a room temperature ionic liquid (RTIL) using five N-pivot tripodal diglycolamide ligands (L I -L V ) having different structural features, viz. spacer lengths and substituents. The nature of the metal/Ligand complex changed with the substitution of N atom near the tripodal platform from ML with L III and L IV to ML 2 with L I , L II and L V (where M = Eu 3+ /Nd 3+ /Am 3+ ). With 0.2 mmol/L ligands, the distribution ratio of Am 3+ at 1 M HNO 3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, it is extremely difficult to separate Ans­(III) from Lns­(III) efficiently and conveniently. It is believed that the separation of Lns­(III) and Ans­(III) with specifically designed ligands is an efficient and convenient method. , Researchers have developed a series of ligands and studied their applications in the separation of Lns­(III) and Ans­(III), such as trialkylphosphine oxide (TRPO), , N,N,N′,N′ -tetraoctyl diglycolamide (TODGA), , and di­(2-ethylhexyl)­phosphoric acid (HDEHP). Due to the demand for the “CHON” principle and high selectivity, nitrogen heterocyclic ligands, , such as 2,6-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-pyridine (BTP), 6,6′-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-2,2′-bypyridine (BTBP), , and 2,9-bis­(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhen), are considered to be the most promising ligands for research and application. Therefore, to design a potential ligand to separate Ans­(III) over Lns­(III) with high efficiency and selectivity, our laboratory has successfully synthesized and characterized a novel lipophilic ligand, Et-Tol-DAPhen, which is applied in the selective separation of actinides over Eu­(III) in a highly acidic environment. …”
Section: Introductionmentioning
confidence: 99%
“…However, it is extremely difficult to separate Ans­(III) from Lns­(III) efficiently and conveniently. It is believed that the separation of Lns­(III) and Ans­(III) with specifically designed ligands is an efficient and convenient method. , Researchers have developed a series of ligands and studied their applications in the separation of Lns­(III) and Ans­(III), such as trialkylphosphine oxide (TRPO), , N,N,N′,N′ -tetraoctyl diglycolamide (TODGA), , and di­(2-ethylhexyl)­phosphoric acid (HDEHP). Due to the demand for the “CHON” principle and high selectivity, nitrogen heterocyclic ligands, , such as 2,6-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-pyridine (BTP), 6,6′-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-2,2′-bypyridine (BTBP), , and 2,9-bis­(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhen), are considered to be the most promising ligands for research and application. Therefore, to design a potential ligand to separate Ans­(III) over Lns­(III) with high efficiency and selectivity, our laboratory has successfully synthesized and characterized a novel lipophilic ligand, Et-Tol-DAPhen, which is applied in the selective separation of actinides over Eu­(III) in a highly acidic environment. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a tripodal amide ligand with a C -atom at the center should be quite useful as it does not have a lone electron pair. It is important to mention that the C -pivoted tripodal diglycolamide (termed as T-DGA) has been reported to be far more efficient than the N -pivoted tripodal diglycolamide (termed as TREN-DGA). In view of this, it was decided to synthesize two C -pivoted tripodal amides with varying spacer lengths. Figure gives the structures of two tripodal amides L I and L II with spacer lengths of 3 and 4, respectively (number of atoms in between the central carbon atom and the carbonyl carbon atom).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Although the linear-chain DGA ligand, N,N,N′,N′-tetra-noctyl diglycolamide (TODGA), has been extensively studied for the separation of trivalent actinides and lanthanides from acidic feed conditions akin to those of the HLLW, recent studies have shown that the ligand extraction efficiency increases manyfold when multiple DGA units are functionalized onto a suitable scaffold. 10 Consequently, a host of multiple DGA ligands were evaluated with tripodal configurations where three constituent DGA units were attached to a carbon center (C-tripodal DGA), 11,12 a nitrogen center (Ntripodal DGA), 13,14 or a benzene center. 15,16 These tripodal multiple DGA ligands show varying degrees of extraction efficiencies and selectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Although the linear-chain DGA ligand, N , N , N′ , N ′-tetra- n -octyl diglycolamide (TODGA), has been extensively studied for the separation of trivalent actinides and lanthanides from acidic feed conditions akin to those of the HLLW, recent studies have shown that the ligand extraction efficiency increases manyfold when multiple DGA units are functionalized onto a suitable scaffold . Consequently, a host of multiple DGA ligands were evaluated with tripodal configurations where three constituent DGA units were attached to a carbon center (C-tripodal DGA), , a nitrogen center (N-tripodal DGA), , or a benzene center. , These tripodal multiple DGA ligands show varying degrees of extraction efficiencies and selectivities. In this series, a tripodal DGA functionalized to a triaza-9-crown-3 scaffold, named as TAM-3-DGA, has shown very efficient affinity for trivalent actinides and lanthanides vis-à-vis the C-tripodal or N-tripodal DGA ligands. In addition to the better extraction efficiency of TAM-3-DGA ligands for trivalent f -block elements, these ligands show poor extraction for uranyl ions as compared to linear-chain TODGA, thus giving better separation factors for Am 3+ , Eu 3+ , Np 4+ , and Pu 4+ ions over UO 2 2+ ion.…”
Section: Introductionmentioning
confidence: 99%